PELAKSANAAN UNDANG-UNDANG NOMOR 38 TAHUN 1999 TENTANG PENGELOLAAN ZAKAT OLEH BADAN AWL ZAKAT PEMERINTAH KABUPATEN SLEMAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The research results show that method of zakah collecting is based on promissory note to pay zakah (from a state official) or take directly (from the others), and the distributing of zakah is based on a proposal that be accepted by the Board. To hold responsible for public, the Board gives a zakah managing report to muzakki and to local parliament. The pursue factors of the board to execute the Act number 38 year 1999 are (1) the staff are nor profesÂ¬sional, (2) the facility is not enough, and (3) the leadership is not participative. On the other hand, the supporting factor of the board to do their task is political supporting of Sleman Regency Government for those board.